"Let's talk about the real issue": Localized perceptions of environment and implications for ecosocial work practice. Issue 3 (2nd October 2019) - Kang, Joonmo; Fabbre, Vanessa D.; Ekenga, Christine C.
ABSTRACT: This interpretive study investigated how residents from socioeconomically challenged communities in North St. Louis understand and make meaning of environmental change and its impact on their well-being. Based on these localized data, we argue that racial minorities facing socioeconomic challenges may experience some environmental issues as less of an immediate concern than violence and racism. However, race and racism shape both the realities of environmental threats as well as residents' perceptions about environmental injustice in their communities. This study informs ecosocial work practices such as educating communities on local environmental issues and mobilizing community members toward environmental decision-making.